EVIDENCE-BASED POLICING the basics. - Ratcliffe, Jerry ([S.l.] : ROUTLEDGE, 2023)
What is evidence-based policing and how is it done? This book provides an answer to both questions, offering an introduction for undergraduate students and a hands-on guide for police officers wanting to know how to put principles into practice. It serves as a gentle introduction to the terminology, ideas, and scientific methods associated with evidence-based policy, and outlines some of the existing policing applications. A couple of introductory chapters summarize evidence-based policy and its goals and origins. The core of the book eases the reader through a range of practical chapters that answer questions many people have about evidence-based practice in policing. What does good science look like? How do I find reliable research? How do I evaluate research? What is a hypothesis? How do randomized experiments work? These chapters not only provide a practical guide to reading and using existing research, but also a roadmap for readers wanting to start their own research project. The final chapters outline different ways to publish research, discuss concerns around evidence-based policing, and ask what is in the future for this emerging field. Annotated with the author's own experiences as a police officer and researcher, and filled with simple aids, flowcharts, and figures, this practical guide is the most accessible introduction to evidence-based policing available. It is essential reading for policing students and police professionals alike. Further resources are available on the book's website at evidencebasedpolicing.net.
Keywords: Police; Police administration; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement; POLITICAL SCIENCE / Public Affairs & Administration; SOCIAL SCIENCE / Criminology